color methodology to Re-reading the musical notes (Al-Academy, 2022)
many painters tried to mix colors with Music by direct employment through colorful musical pieces or the use of multiple instruments and techniques , or vice versa, including the French artist )Robert Stroben(, he transferred the piece of music to be depicted on the painting and worked on the tones of music (Johann Sebastian Bach) by dropping the color on the lines of the musical scale, for example (the C tone) ranging from brown to red ( Tone La A) from gray to orange, and so on, the presence of links and similarity factors between the world of music and the world of colors facilitated the process of linking musical notes with colors, the most famous of which was presented by the world (Newton) in the circle of basic colors and linking them with musical notes (Du tone = violet color) - (Ri tone = indigo color) - (Mi tone = blue color) - (Fa tone = green color) - (Sol tone = yellow color) - (La tone = orange color) - (C tone = red color). But this circuit is not enough in converting the musical note to a specific color. It is one of the basics of musicology. The notes are repeated in every (octave) but by increasing the speed of their frequencies. The melodies are based on the major scales, which seem bright, cheerful and optimistic, while the minor scales (miner) seem bleak. Serious and sad. This is what the German scientist (Goethe) sees as there is a similarity between the two worlds of colors and music. In the “melody field” we find the two musical scales (small and large) or what is known as (major and minor), and he sees the contrast between them in the “color field” in degrees of lightness and darkness. On the other hand, we find that colors differ in their energies according to color, as the scientist (Munsel) introduced the color measurement system through (the color is H, the amount of its saturation S and the amount of luminance v), and when creating a (Munsell) of colors, we find that it is not symmetrical, so pure, saturated red extends farther From the central axis about greenish-blue, as well as for the value (V), the blue-purple colors reach their full saturation when the value (V) is very low, and some colors such as yellow retain a high value (V) and high saturation. Therefore, the result of a (genus) is a three-dimensional quasi-spherical solid. According to the above, a color model representing the musical notes was formulated according to their position from the octave and according to their presence in a high or low scale, and the frequency of the sound wave was calculated, corresponding to the amount of the corresponding light wave frequency divided by (terra) /(107) multiplied by x(1.05) And it was applied in the samples of this research.